Hemimandibulectomy of mandibular large odontogenic myxofibroma in adolescence girl and immediate reconstruction with AO plate - Victor T. Pamolango; Agus Nurwiadh; Melita Sylvyana; Alwin Kasim (DiscoverSys Inc., 2016)
Odontogenic myxofibroma is a rare, benign, but locally aggressive neoplasm found exclusively in the jaws. It has a predilection to occurs in the 2nd–3rd decade. The lesion often grows without symptoms and presents as a painless swelling. Most common clinical variant is associated with the impacted tooth and shows local invasion. The surgical treatment of these tumors consists of complete enucleation or radical excision. 15th year old girl with a slow growing, painless swelling in the left mandibular region since 2 years. Results of a radiological examination revealed a multilocular radiolucency extending from first molar up to coronoid process with impacted 3rd molar. Biopsy was done, and the histopathological examination showed a myxofibroma. Hemimandibulectomy was done and the tumor mass was resected along with it. Then the mandibular was reconstructed with AO plate. In this case hemimandibulectomy was done due to high rate of recurrence, surgical treatment through bone resection is the most indicated treatment modality and the patient must be followed‑up closely for years. AO Plate for mandibular reconstruction was considered because it was safe, rapid, easy and tissue tolerance is good. The neoplasm diagnosed on the basis of radiographic imaging modalities and histopathological examination.